Kaposi sarcoma can also involve the heart - Mohamad Hani Lababidi; Hazem Alhawasli; Nkemakolam Iroegbu (Greater Baltimore Medical Center, 2015)
Kaposi sarcoma (KS) is a low-grade angioproliferative tumor associated with infection with human herpes virus 8 (HHV-8). The disease was named after Moritz Kaposi, a Hungarian dermatologist who first described it in 1872 as 'idiopathic multiple pigmented sarcoma of the skin.' HHV-8 infection is required for the development of KS, but not all infected persons develop the disease. KS is also considered an acquired immune deficiency syndrome (AIDS)-defining illness by the Centers for Disease Control and Prevention guidelines. According to data from the United States AIDS and cancer registries, both KS and non-Hodgkin lymphoma are the most common malignancies associated with human immunodeficiency virus (HIV) infection. However, the incidence of both malignancies has decreased dramatically since 1996 following the widespread utilization of highly active antiretroviral therapies. HIV-associated KS can involve virtually any site in the body including lymph nodes, gastrointestinal tract, respiratory system, heart, pericardium, bone marrow, and other visceral organs. However, cutaneous disease is the most common and is the usual initial presentation for KS. KS-related pericardial effusion can be a life-threatening emergency and should be considered in HIV/AIDS patients who present with signs and symptoms of pericardial effusion. The importance of diagnosing and differentiating KS-related pericardial effusion from other causes of pericardial effusion lies in the differences in the treatment and management in comparison to other etiologies of pericardial effusion. We report a case of a 54-year old man who presented to our hospital with a large pericardial effusion and was subsequently diagnosed to have HIV-related KS pericardial effusion. A brief review of the literature on the diagnosis and management is also presented.